The stele of Polybios: art, text and context in second-century BC Greece - Melfi, M (De Gruyter, 2017)
Two large stelai were erected in Mantinea and Kleitor, in Arkadia, in honour of the historian Polybios. They both bore identical inscriptions in verse: τοῦτο Λυκόρτα παιδὶ πόλις περικαλλὲς ἄγαλμα| ἀντὶ καλῶν ἔργων εἵσατο Πουλυβίωι (the polis for the son of Lykortas set up this excellent statue, for Polybios in change of his good deeds). The inscribed fragment from Mantinea was found in secondary use near the agora of the city in the 1890s, and only measures 25x27 cm, but its profile allowed the first editor to conclude without doubt that it originally formed part of a stele . The stele from Kleitor has similarly been known since the 19th century, is extraordinarily large (218x111 cm), in relatively low relief, and almost complete (Figs. 1 and 2). It depicts a warrior, almost 2 m tall, wearing an exomis belted at the waist and a long mantle clasped on his right shoulder. The man raises his right hand high, palm outward, while holding a spear and the rolled lower part of his mantle in his left. A large round shield and a crested helmet rest on the ground. A sword is strapped across his chest . The text is unfortunately very fragmentary, but was fully reconstructed, already at the time of its discovery, on the basis of two later inscriptions from Olympia, honouring a descendent of Polybios . Both the lettering of the inscriptions and the figurative relief preserved in the stele from Kleitor are perfectly compatible with a late Hellenistic date and it is generally agreed that they should be considered roughly contemporary to Polybios’ activity in Greece. This is to be placed either before 168 BC, when his career of military and political leader of the Achaean league was cut short by his deportation to Rome, or in the years 146-145 BC, when he was sent to Greece from Rome shortly after the sack of Corinth and the defeat of the Achaean League in order to facilitate the political transition of the Greek cities to Rome’s control. Some aspects of this intriguing evidence have been considered recently in works by Anna Heller and John Ma .